Evaluation of the safety, gastroprotective activity and mechanism of action of standardised leaves infusion extract of Copaifera malmei Harms. (4th December 2015) - Adzu, Bulus; Balogun, Sikiru Olaitan; Pavan, Eduarda; Ascêncio, Sérgio Donizeti; Soares, Ilsamar Mendes; Aguiar, Raimundo Wagner Souza; Ribeiro, Reginaldo Vicente; Beserra, Ângela Márcia Selhorst e Silva; de Oliveira, Ruberlei Godinho; da Silva, Larissa Irene; Damazo, Amílcar Sabino; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Copaifera malmei Harms (Fabaceae) is a plant that occurs in the central region of Brazil, where the plant's leaves infusion is popularly used to treat gastric ulcer and inflammatory diseases. This study was aimed to investigate the gastroprotective activity and mode of action of the plants' leaves infusion in order to establish the scientific basis for such usage, and to assess its potential as a source of an anti-ulcer agent. Materials and methods: Leaves infusion extract of the plant (SIECm) was prepared, freeze dried and lyophilised. Its qualitative and quantitative phytochemical constituents were investigated using TLC and HPLC techniques. The safety profile was evaluated on CHO-k1 epithelial cells viability using the Alamar blue assay, and by acute toxicity test in mice. The gastroprotection and anti-ulcer efficacy of the SIECm (25, 100 and 400 mg/kg, p.o.) were tested using acute (acidified ethanol, piroxicam and water restrain stress), and chronic (acetic acid) experimental ulcer models. The plausible mode of action of the SIECm was assessed using gastric secretion, gastric barrier mucus, nitric oxide, and its antioxidant (myeloperoxidase and catalase) effects in mice and rats. The histopathological analyses of the ulcerated tissues as well as the extract's activity on Helicobacter pylori were also investigated. Results: Phytochemical tests indicated the presence of mainly phytosterols, phenolics and flavonoids. The SIECm exhibited no cytotoxic effects on the CHO-k1 cells, and no oral acute toxicity in mice. It prevented against the acute induced ulcerations by enhancing gastroprotection through gastric mucus production, NO modulation, antioxidant, reduced gastric secretion and enhanced chronic ulcers healing process, as shown by reduction/prevention of epithelial and vascular damage, in addition to reduction in leucocyte infiltration. The SIECm however did not exhibit activity against H. pylori . Conclusion: The SIECm is safe, contain useful phytochemicals and exhibited significant gastroprotective/anti-ulcer effects. The results justify its folkloric usage, and provided scientific evidence of its potential as a source of new phytodrug to treat gastric ulcers. Graphical abstract: